The role of environmental tobacco exposure and Helicobacter pylori infection in the risk of chronic tonsillitis in children - Li’e, Chen; Dongying, Jiang; Dongying, Jiang; Guiling, Feng; Tihua, Zheng; Yanfei, Wang (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Helicobacter pylori (H. pylori) is a chronic infectious pathogen with high prevalence. This study investigated the interaction between environmental tobacco exposure and H. pylori infection on the incidence of chronic tonsillitis in Chinese children. DESIGN AND SETTING: Cross-sectional study performed in an outpatient clinic in China. METHODS: Pediatric patients with chronic tonsillitis were enrolled. H. pylori infection was determined according to the presence of H. pylori CagA IgG antibodies. Serum cotinine levels and environmental tobacco smoke (ETS) exposure were determined for all participants. RESULTS: There was no significant difference in H. pylori infection between the children with chronic tonsillitis and children free of disease, but there was a significant difference in ETS between the two groups (P = 0.011). We next studied the association between ETS and chronic tonsillitis based on H. pylori infection status. In the patients with H. pylori infection, there was a significant difference in ETS distribution between the chronic tonsillitis and control groups (P = 0.022). Taking the participants without ETS as the reference, multivariate logistic regression analysis showed that those with high ETS had higher susceptibility to chronic tonsillitis (adjusted OR = 2.33; 95% CI: 1.67-3.25; adjusted P < 0.001). However, among those without H. pylori infection, ETS did not predispose towards chronic tonsillitis. CONCLUSION: Our findings suggest that tobacco exposure should be a putative mediator risk factor to chronic tonsillitis among children with H. pylori infection.